A humanização nos processos de trabalho de um centro de atenção secundária - Dode, Maria Teresa Bicca (Universidade do Vale do Rio do Sinos, 2009)
Humanization is a cross-cutting policy of all National Health System that aims to integrate the different levels of care. Without a networking can not be humanization.The weak link of this network about humanization is the secondary level of care. This study aims to understand precisely the humanization in secondary care and customer service, and as a process of networking. For this, we interviewed 10 professionals from different specialties working in the clinic of the Catholic University of Pelotas. Results showed that secondary care as a service is characterized as fragmented and disjointed from primary care and hospital care, despite being regarded as key link in the health system. Furthermore, secondary care as work process has a hospital-feature, emphasizing the technical nature and hierarchy, making hard a health care designed as a whole. It is evident the importance of a systemic view of health and the need for changes in work processes.
Keywords: atenção secundária; processos de trabalho; humanização; secondary care; work processes; humanization; Ciências da Saúde